Letter : Voluntary industrial aid - Wolstencroft, Frank
036-0041-001 Telegrams:"COHESIVE, Withington,Lancs". Telephone No. DIDSBURY 3103. Amalgamated Society of Woodworkers. GENERAL OFFICES, FW/DK. 131,Wilmslow Road, Withington, Manchester. 17th April, 1937. Your Reference:- WMC/WJB/AC/632. Dear Sir, VOLUNTARY INDUSTRIAL AID. With respect to the above as referred to in your letter of the 15th April, I was directed by my Executive Council to inform you that it cannot agree to the scheme in its full application, neither is it agreeable to being represented on the Advisory Committee of this Organisation. My Executive Council has no objection to raise against any member of our Society as individuals, (but not as representing the A.S.W.) voluntarily engaging in this scheme. Yours sincerely, F. Wolstencroft GENERAL SECRETARY. Sir Walter Citrine, Secretary, Trades Union Congress General Council, Transport House, Smith Square, London. S.W.1. 292/946/36/41